Peran dan Kontribusi Badan Usaha Milik Desa (BUMDes) Terhadap Kesejahteraan Masyarakat Desa Menurut Ekonomi Islam : Studi Kasus Badan Usaha Milik Desa (BUMDes) Mutiara Welirang Desa Ketapanrame - Fikri Alfan; Diah Syifaul A’yuni; Nadya Khoirun Nisa’ (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study employed qualitative methods with primary and secondary data sources. Primary data were obtained through interviews, while secondary data were obtained from important documentation of the Mutiara Welirang Village-Owned Enterprise (BUMDes). Data analysis was conducted using descriptive qualitative methods to obtain a comprehensive picture of the BUMDes' contribution to community welfare. The results of the study indicate that the Mutiara Welirang BUMDes plays an active role in improving the welfare of the Ketapanrame Village community through various services. These services include clean water management, environmental cleanliness management, interest-free loans, stall and kiosk rentals, and tourist attraction management. These various services are considered to have a positive impact on the social and economic conditions of the village community. An Islamic Economics review of the BUMDes' contribution indicates its alignment with Islamic economic principles. The activities carried out are mutually beneficial and align with Islamic values and welfare indicators in the maqashid sharia. This reflects the application of the values of justice, balance, and sustainability in village economic practices. The implications of these findings suggest that the Mutiara Welirang BUMDes can continue to maintain its positive performance and continuously improve the quality of its services. This effort is crucial to ensure the benefits are felt more widely by the community and to further strengthen the role of BUMDes as a driver of village economic development based on Islamic values.